Stand Against Bullying: An Experimental School Intervention - Italo A. Gutierrez; Oswaldo Molina; Hugo R. Nopo (Institute of Labor Economics (IZA), 2018)
Despite the growing evidence on the negative consequences of school bullying, there is no consensus regarding the most effective strategies to fight this problem. We study the impact of a randomized intervention to reduce school bullying in urban public schools in Peru, a country where violence re-mains a major challenge. The intervention consisted of two components: i) increasing awareness among students about the negative consequences of bullying and encouraging them to stand against this problem, and ii) facilitate students' ability to report violent incidents, by promoting the use of a new Government program for submitting online confidential reports. Our results indicate that the intervention reduced students' bystander behavior and increased their willingness to report violence. Using administrative data, we also find that the intervention reduced the likelihood of changing schools and of dropping out, and improved student achievement in standardized tests in the medium term. Importantly, we find that the intervention had a more limited impact among children that are exposed to violence at home. While depression and isolation were significantly reduced among non-exposed students, this effect disappears among children living in a violent environment. Overall, these findings are promising and reveal that encouraging students to stand up against bullying and providing them with the means to do it may have beneficial effects over their well-being and educational performance, even in violent settings.
Keywords: D04; I20; I28; 330; school violence; anti-bullying programs; student achievement; school dropout; randomized control trial; Peru